STUDENTS’ PERCEPTIONS TOWARD NATIVE ENGLISH SPEAKER-TEACHER’S (NEST) AND NON-NATIVE ENGLISH SPEAKER TEACHER’S (NNEST) ATTITUDES AND PERFORMANCES (RETAIN, 2014)
Abstrak Persepsi adalah sebuah pandangan yang diperoleh terhadap sesuatu setelah mengalaminya. Persepsi siswa dapat menjadi evaluasi siswa untuk guru selain nilai test. Siswa yang tidak mempunyai kemauan untuk belajar dengan guru mata pelajarannya pasti tidak akan mempunyai ketertarikan terhadap pelajaran tersebut. Melalui persepsi siswa, guru dapat mengetahui apa yang dibutuhkan siswa. Oleh karena itu, penelitian tentang persepsi siswa sangat berguna untuk menghasilkan pengajaran yang efektif Centra & Gaubatz (2005). Untuk mendapat deskripsi keseluruhan persepsi siswa, peneliti merancang tiga rumusan masalah, diantaranya (1) Bagaimana persepsi siswa terhadap NEST dibanding NNEST dalam hal teaching attitudes? (2) Bagaimana persepsi siswa terhadap NEST dibanding NNEST dalam hal teaching performances? (3) Apakah implikasi dari persepsi siswa terhadap terhadap NEST dan NNEST dalam hal teaching attitudes dan teaching performances pada proses belajar mengajar di SMK Negeri 1 Kemlagi Mojokerto? Penelitian ini dilakukan untuk mendeskripsikan persepsi siswa terhadap NEST dan NNEST dalam hal teaching attitudes dan teaching performances di SMKN 1 Kemlagi menggunakan penelitian deskriptif kualitatif. Kuisioner digunakan untuk mengumpulkan tiap-tiap persepsi siswa terhadap attitudes dan performances dari NEST dan NNEST sedangkan wawancara digunakan untuk mengumpulkan persepsi siswa lebih rinci. Hasil dari penelitian menunjukkan bahwa persepsi siswa sejalan dengan penelitian yang dilakukan oleh Medgyes (1992) pada umumnya. Akan tetapi, peneliti menemukan beberapa perbedaan teaching attitudes dan teaching performances dengan penelitian yang telah dilakukan oleh Medgyes (1992) dan Floyd (2007) dalam hal the practice of grammar, vocabulary teaching and their discipline about time management. Dalam hal ini, peneliti menyimpulkan bahwa persepsi siswa dapat juga digunakan sebagai pertimbangan guru untuk mengembangkan metodenya untuk tidak hanya membuat proses belajar mengajar menyenangkan, akan tetapi juga mencapai tujuan pembelajaran. Kata Kunci: persepsi siswa, NEST’s and NNEST’s attitudes, NEST’s and NNEST’s performances. Abstract Perception is a notice that comes up after undergoing some experiences. Students’ perception can be one of students’ evaluation for the teacher instead of final examination or final test score. Students who do not have a desire to join the class of some of their course teachers, especially English will not have an interest feeling in the subject. Through students’ perception, teacher is able to know what the students’ need. Hence, study about students’ perception is useful to create an effective teaching Centra & Gaubatz (2005). To describe the whole students’ perception, reseacher set three research questions. They are: (1) What are students’ perceptions on NEST in comparison to non-NEST in terms of their teaching? (2) What are students’ perceptions on NEST in comparison to non-NEST in terms of their teaching performances? (3) What is the implication of students’ perceptions on NEST and non-NEST in terms of their teaching attitudes and teaching performances on the teaching-learning process? This study was conducted to describe the students’ perceptions toward NEST and NNEST in terms of their teaching attitudes and their teaching performances in SMKN 1 Kemlagi using descriptive qualitative research design. Questionnaire was used to collect every single students’ perception toward their NEST’s and NNEST”s attitudes and performances while the interview was used to collect students’ perception in detail. The results of this study shows that students’ perceptions were generally in line with the general perception of both NESTs and NNESTs suggested by Medgyes (1992). However, researcher found some different teaching attitudes and teaching performances was found in this study that is in contrary with the findings of study conducted by Medgyes (1992) and Floyd (2007) concerning on the practice of grammar, vocabulary teaching and their discipline about time management. It is suggested that students’ perception can also be used as teacher’s consideration in the term of developing his or her methods to not only be pleasant learning but also achieves the goal of the study. Keywords: students’ perceptions, NEST’s and NNEST’s attitudes, NEST’s and NNEST’s performances.